Enforcement Mechanisms of the Legal Obligations in Public Procurement- Comparative Study - Hassan, Ahmed Aziz; Abdulla, Dawan Muhammad Jaza; Othman, Arez Mohammed Sediq (Sulaimani Journal for Humanities, 2021)
The key feature of an effective procurement regime is the existence of certain mechanisms to be followed in order to guarantee the implementation of the rules and to enforce them when necessary. Therefore, it is essential to have some rules and procedures to make sure that the procuring entity takes the right path in the activities related to public procurement and allowing the participants (bidders) to challenge the non-compliance decisions of the procuring entity on the legal grounds when their rights are violated and to accomplish the transparency and accountability requirements of the public procurement policy. This research evaluates the Iraqi law provisions related to enforcement mechanisms and compares them with the European Union standards, the Agreement on Government Procurement (GPA) and the United Nations Commission on International Trade Law Model Law on Public Procurement (UNCITRAL Model Law on Public Procurement). Finally it recommends some changes to be made in the shortcoming aspects of the related laws in Iraq.